Kebolehan Suami Memukul Istri Yang Nusyûz Dalam Al-Qur’an - Sri Wihidayati (Institut Agama Islam Negeri Curup, 2017)
One of the negative allegations against Islam, especially from the Western (orientalist) is that Islam is a religion that tends to justify violence. The allegations are reasonable. One of them is because in Islam there is a doctrine which, if not studied in fully and deeply, gives the impression of the existence of acts of violence. For example, there is an al-Qur'an letter of al-Nisa '/ 4: 34 that allows husbands to beat wives who do nusyz to them. To verify whether or not the allegations are alleged, Q.S al-Nisa'/4:34 needs to be examined critically, profoundly and comprehen-sively. Having studied with the analytical approach of tahlîlî, it does not or does not mean justification of violence, but rather.